2017
DOI: 10.24106/kefdergi.309192
|View full text |Cite
|
Sign up to set email alerts
|

Yöneti̇ci̇ Öz-Yeterli̇ği̇ Ve Okul Etki̇li̇li̇ği̇ Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇

Abstract: Özet Bu araştırmanın temel amacı okul yöneticilerinin yönetici öz-yeterlik algıları ile okul etkililiği arasındaki ilişkiyi incelemektir. Araştırmanın çalışma grubunu AbstractThe aim of this research is to determine the relationship between principals' self efficacy and school effectiveness. The research sample consists of 199 school principals. In the study, in order to determine principals self-efficacy, "Principal Sense of Efficacy Scale" which was developed by Tschannen-Moran and Gareis (2004) and adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…In the current study, it is seen that the school principals' self -efficacy perceptions are high. When the previos studies are examined; Baltacı (2017b), Bayraktar (2020), Cobanoglu and Yurek (2018), Işık and Gümüş (2016), İnandı et al, (2015), Karatepe and Uzun (2015), Köybaşı and Dönmez (2017), Okutan and Kahveci (2012) and Özer (2013) reached similar results in their studies. Baltacı (2017a), on the other hand, concluded that school principals' self-efficacy is low.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 64%
“…In the current study, it is seen that the school principals' self -efficacy perceptions are high. When the previos studies are examined; Baltacı (2017b), Bayraktar (2020), Cobanoglu and Yurek (2018), Işık and Gümüş (2016), İnandı et al, (2015), Karatepe and Uzun (2015), Köybaşı and Dönmez (2017), Okutan and Kahveci (2012) and Özer (2013) reached similar results in their studies. Baltacı (2017a), on the other hand, concluded that school principals' self-efficacy is low.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 64%
“…According to our research, school size has a moderating effect on the relationship between the school administrator's leadership behaviors and school effectiveness. When the literature was examined, it was stated that there was no statistically significant relationship between binary correlations such as school size and school effectiveness (Işık and Gümüş, 2017) and school size and leadership (Aksoy and Işık, 2008;Dağlı and Ağalday, 2018;Hiçyılmaz, 2013;Namlı, 2017). In the studies examining regulatory effects, it is emphasized that school size has a regulatory role on leadership behaviors (Dadkhah et al, 2014;Wu et al, 2020).…”
Section: Extended Summarymentioning
confidence: 99%
“…Cerit ve Yıldırım'ın (2017) araştırmasında da okul etkililiği orta düzeye yakın olarak tespit edilmiştir. Ayrıca bazı araştırmalarda okul müdürlerinin görüşlerine göre de okul etkililiğinin yüksek olduğu görülmüştür (Işık & Gümüş, 2016;Yürek & Cömert, 2021). Literatürde okul etkililiğinin farklı örneklemlerde incelenmesi konunun güncelliğini ve önemini işaret etmektedir.…”
Section: Bulgular Betimsel İstatistiklerunclassified